A novel RNA-binding motif in omnipotent suppressors of translation termination, ribosomal proteins and a ribosome modification enzyme? - Koonin, E V (1994)
Using computer methods for database search, multiple alignment, protein sequence motif analysis and secondary structure prediction, a putative new RNA-binding motif was identified. The novel motif is conserved in yeast omnipotent translation termination suppressor SUP1, the related DOM34 protein and its pseudogene homologue; three groups of eukaryotic and archaeal ribosomal proteins, namely L30e, L7Ae/S6e and S12e; an uncharacterized Bacillus subtilis protein related to the L7A/S6e group; and Escherichia coli ribosomal protein modification enzyme RimK. We hypothesize that a new type of RNA-binding domain may be utilized to deliver additional activities to the ribosome.